Correlações entre sono-vigília, memória e melatonina em Síndrome de Williams-Beuren - Santoro, Stella Donadon [UNESP] (2014)
The Williams-Beuren syndrome (WBS), caused by a microdelection in the chromosomal region 7q.11.23, shows a phenotype as typical facial features, short stature, cardiovascular abnormalities and connective tissue disorders, cognitive profile and unique personality, besides intellectual disability in different degrees. Recent studies reported high prevalence of sleep problems in this population which may indicate a possible biological rhythm disorder in these individuals, worsening their behavior and learning problems. Despite the negative consequences of sleep disorders on cognitive performance and behavioral aspects, few studies have explored this issue and it is unclear whether the sleep-wake pattern is correlated with behavioral patterns in WBS. Sleep is a biological phenomenon controlled by a complex neural network consisting of signaling pathways and regulatory processes in molecular, cellular and organismic levels. In this scenario, melatonin, a hormone produced by the pineal gland during the dark, has been showed important for the initiation, maintenance and quality of sleep, and that changes in its synthesis are often associated with the causes of sleep disorders. Sleep disorders can be related with memory problems, component of the WBS phenotype. Therefore this study is aimed at characterizing the pattern of sleep-wake behavior, assess levels of attention and memory, and correlate them to melatonin levels in WBS. The study group (GP) consisted of 15 children 6-17 years old with WBS, and the control group (GC) composed of 15 children matched for age, with no history to genetic disorders, or neurological changes in cognitive and motor development. For data collection, were used the Sleep Disturbance Scale for Children (EDSC), the Child Behavior Checklist for ages 6-18 (CBCL) parents version, WISC-III and WAIS-III for the characterization of cognitive abilities, visual sequential memory subtest of the brazilian 13 version of the Illinois...